2020
DOI: 10.1016/j.omto.2020.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic Activity of Targeted Picornaviruses Formulated as Synthetic Infectious RNA

Abstract: Infectious nucleic acid has been proposed as a superior formulation for oncolytic virus therapy. Oncolytic picornaviruses can be formulated as infectious RNA (iRNA), and their unwanted tropisms eliminated by microRNA (miRNA) detargeting. However, genomic insertion of miRNA target sequences into coxsackievirus A21 (CVA21) iRNA compromised its specific infectivity, negating further development as a novel oncolytic virus formulation. To address this limitation, we substituted a muscle-specific miRNA response elem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…As a possible reason for these observations, He et al suggested that the miR-TS probably disturbed the higher-order RNA structure of the viral genome [ 137 ]. This assessment is in line with another report showing delayed propagation of CVA21 from infectious viral RNA after insertion of miR-TS into a stem loop structure of the 3′-UTR which is important for viral RNA synthesis and poly(A) tail elongation [ 139 ]. Nevertheless, several studies recently demonstrated that miR-TS can also be inserted into the 3′-UTR of CVB3 without affecting virus propagation.…”
Section: Improvement Of the Safety Of Oncolytic Cvb3 By Microrna-mediated Regulation Of Virus Replicationsupporting
confidence: 91%
“…As a possible reason for these observations, He et al suggested that the miR-TS probably disturbed the higher-order RNA structure of the viral genome [ 137 ]. This assessment is in line with another report showing delayed propagation of CVA21 from infectious viral RNA after insertion of miR-TS into a stem loop structure of the 3′-UTR which is important for viral RNA synthesis and poly(A) tail elongation [ 139 ]. Nevertheless, several studies recently demonstrated that miR-TS can also be inserted into the 3′-UTR of CVB3 without affecting virus propagation.…”
Section: Improvement Of the Safety Of Oncolytic Cvb3 By Microrna-mediated Regulation Of Virus Replicationsupporting
confidence: 91%
“…miRNA connects lncRNA and mRNA in various cancers, including HCC, acting as a bridge for the ceRNA network. 78 , 79 , 80 , 81 miR-96 reduces HCC migration, functioning as a therapeutic target in this disease. 82 miR-221-3p promotes HCC by downregulating the expression of O6-methylguanine-DNA methyltransferase.…”
Section: Discussionmentioning
confidence: 99%
“…miRNA-targeting elements inserted within the viral genome target picornaviruses for degradation in healthy tissues expressing the cognate miRNA, while replication occurs unencumbered in neoplastic tissues where the cognate miRNA is not expressed [ 116 ]. This approach was shown to reliably eliminate fatal CAV21-associated myotoxicity in OV mouse models, both in the infectious RNA and viral particle formulation [ 117 119 ]. The use of miRNA-targeting elements not only controls oncolytic picornavirus permissivity and hence tissue-specific toxicities, but also provides an excellent safety platform to investigate the impact on oncolytic activity of other genome elements.…”
Section: Applicationsmentioning
confidence: 99%